Determinants of Longer Job Tenure Among Home Care Aides: What Makes Some Stay on the Job While Others Leave?. (March 2014) - Butler, Sandra S.; Brennan-Ing, Mark; Wardamasky, Sara; Ashley, Alison
An inadequate supply of direct care workers and a high turnover rate in the workforce has resulted in a "care gap" in our long-term care system. As people are increasingly choosing community-based care, retention of home care workers is particularly important. The mixed-method study described herein explored determinants of longer job tenure for home care aides ( n = 261). Study participants were followed for 18 months, completing two mail surveys and one telephone interview each. Predictors of longer job tenure included older age, living rurally, lower physical function, higher wages, a greater sense of autonomy on the job, and less frequent feelings of personal accomplishment. Thematic analysis of telephone interviews revealed long-term stayers to be less concerned about low wages and inconsistent hours than those who left their jobs within a year; both groups of workers reported high levels of job satisfaction. Policy implications of study findings are discussed.